2023
DOI: 10.3390/antiox13010023
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidasin Inhibition by Phloroglucinol and Other Peroxidase Inhibitors

Martina Paumann-Page,
Christian Obinger,
Christine C. Winterbourn
et al.

Abstract: Human peroxidasin (PXDN) is a ubiquitous peroxidase enzyme expressed in most tissues in the body. PXDN represents an interesting therapeutic target for inhibition, as it plays a role in numerous pathologies, including cardiovascular disease, cancer and fibrosis. Like other peroxidases, PXDN generates hypohalous acids and free radical species, thereby facilitating oxidative modifications of numerous biomolecules. We have studied the inhibition of PXDN halogenation and peroxidase activity by phloroglucinol and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
0
0
Order By: Relevance
“…Phloroglucinol, a known inhibitor of PXDN [ 163 , 164 ], emerges as a promising compound already formulated for other purposes since a daily intraperitoneal injection of phloroglucinol has been shown to reduce interstitial fibrosis in a mouse model of unilateral ureteral obstruction [ 165 ]. In vitro studies have recently identified new inhibitors of PXDN [ 166 ]. One noteworthy feature of collagen IV is its structural diversity.…”
Section: Indirect Targeting Of Collagen Iv: Protein Folding and Supra...mentioning
confidence: 99%
“…Phloroglucinol, a known inhibitor of PXDN [ 163 , 164 ], emerges as a promising compound already formulated for other purposes since a daily intraperitoneal injection of phloroglucinol has been shown to reduce interstitial fibrosis in a mouse model of unilateral ureteral obstruction [ 165 ]. In vitro studies have recently identified new inhibitors of PXDN [ 166 ]. One noteworthy feature of collagen IV is its structural diversity.…”
Section: Indirect Targeting Of Collagen Iv: Protein Folding and Supra...mentioning
confidence: 99%